Kitāb al-abniya ʿan ḥaqāʾiq al-adwiya : Rawḍat al-uns wa-manfaʿat al-nafs - Hirawī, Abū Mansūr (Miras Maktoob, ISBN: 9789004365452., 2020)
This is a facsimile edition of the oldest dated manuscript in Persian, a pharmacological handbook by Abū Mansūr Hirawī. It was written between 430/1038 and 445/1054 for the local ruler of Ṭāram in the province of Zanjān in north-western Iran, Abū Naṣr Jastān. The present copy was executed in 447/1055 by the poet Asadī Ṭūsī, author of the epic poem Garshāsp-nāma and the oldest Persian dictionary based on samples from poetry, the Lughat-i Furs . Written in a beautiful Khurāsānī Kufic hand, it contains the descriptions and medical properties of 584 simple substances, derived from minerals, animals and plants. Organized on the basis of the Arabic alphabet, it cites besides the Arabic names also many synonyms in Greek, Syrian, Persian, and what is said to be Indian terminology, with several Indian authors referred to by name. Its technical prose combined with local terminology make it a primary source on the history of medicine in Persia.